Old metadata in a new world: Standardizing the Getty Provenance Index for linked data. (October 2019) - Davis, Kelly
Abstract : What challenges does metadata managers face when embarking on a Linked Data transformation? How can legacy projects be better understood to ensure such data remodels stay true to their original content? Current efforts made by the Getty Provenance Index elucidate how this task can be much more than simple data re-structuring, and how much manual and specialized labor goes into updating a 35 year old database.